Minimally invasive TMJ surgery: arthrocentesis x arthroscopy - Figueirêdo , Nathalia Farias Dantas de (2022)
Arthrocentesis and arthroscopy are two minimally invasive surgical procedures designed to treat internal TMJ disorders. This study aimed to compare the pre- and postoperative clinical parameters between the surgical techniques of arthrocentesis and arthroscopy, through a literature review. This is an integrative literature review study, carried out through national and international articles, published in the PubMed, SciELO and CAPES/MEC databases, in the period between 2010 and 2021. Four descriptors were used in Portuguese and English, taken from DeCS. The search for articles was based on the descriptors. After applying the inclusion and exclusion criteria, four articles formed the final sample. Both techniques have excellent success rates in terms of long-term pain relief, immediate improvement in the postoperative period, in mouth opening, as well as in the position of the articular disc. Occurring in low complication rates, which characterizes them as safe procedures. The two techniques demonstrate similarities in success rate with effective results. The choice of the surgical modality should be attributed to the dentist along with the patient, taking into account the evaluation of clinical exams and imaging exams in association with the socioeconomic condition of the patient.